2002
DOI: 10.1089/08942680252908584
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception and Acceptability of Multidose Dry Powder Inhalers: A Randomized Crossover Comparison of Diskus/Accuhaler with Turbuhaler

Abstract: This study was designed to provide information on correct use and preference to features and device handling of two multidose dry powder inhalers, the Diskus/Accuhaler and the Turbuhaler. A total of 169 powder-naive patients (mean age 40 years) with asthma or chronic obstructive pulmonary disease (COPD) were enrolled in a randomized crossover comparison of both inhalers. An effective use of either inhaler was assessed before (leaflet only) and after inhaler education. Ease of use especially during an attack an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 8 publications
(3 reference statements)
2
43
1
9
Order By: Relevance
“…Another randomized crossover study that compared Diskus® and Elpenhaler® device use and included 113 COPD and Asthma patients naive to both inhalers has shown that after reading only PILs 16.8% of Diskus® and 35.4% of Elpenhaler® users made at least one critical error, while the respective percentages after first instruction by the trainer decreased at both patient groups, reaching 1.8% and 11.5% for Diskus® and Elpenhaler® users, respectively [13]. The value of training of inhalation technique is further confirmed by the results of another randomized crossover study that assessed the use of Diskus®/Accuhaler® and Turbuhaler® devices, after PIL reading only and after inhaler education [14]. The results showed that the percentage of correct handling maneuvers and the percentage of patients achieving 100% of correct maneuvers increased significantly after inhaler education in both tested devices.…”
Section: Introductionmentioning
confidence: 70%
“…Another randomized crossover study that compared Diskus® and Elpenhaler® device use and included 113 COPD and Asthma patients naive to both inhalers has shown that after reading only PILs 16.8% of Diskus® and 35.4% of Elpenhaler® users made at least one critical error, while the respective percentages after first instruction by the trainer decreased at both patient groups, reaching 1.8% and 11.5% for Diskus® and Elpenhaler® users, respectively [13]. The value of training of inhalation technique is further confirmed by the results of another randomized crossover study that assessed the use of Diskus®/Accuhaler® and Turbuhaler® devices, after PIL reading only and after inhaler education [14]. The results showed that the percentage of correct handling maneuvers and the percentage of patients achieving 100% of correct maneuvers increased significantly after inhaler education in both tested devices.…”
Section: Introductionmentioning
confidence: 70%
“…Written information such as medication inserts is not enough, and may convey limited and incomplete information. 38,39 In addition, the acquisition of knowledge alone does not necessarily translate into effective self-management behaviors 40 ; physical demonstration of technique with follow-up assessment and education is essential. 3 Hence, we integrated hands-on education for HCPs into the workshop following the "train the trainer" approach; this is essential for HCPs to develop their own skills, so they can in turn educate patients to insure effective self-management behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Although factors such as age, marital status, socioeconomic status, and education level also play a role in patient adherence to aerosol therapy, they do not provide obvious predictors. 19,54,55 On the other hand, depression is an important factor causing nonadherence to prescribed medication and poor disease management in patients with pulmonary disorders such as COPD. [56][57][58] Previous research has shown that adherence to Failing to prime the device, using the device after it is empty, exhaling through the device before inhalation, failing to inhale forcefully pMDIs ϭ pressurized metered-dose inhalers DPIs ϭ dry powder inhalers prescribed medication is an issue especially in low-income and minority subjects.…”
Section: Factors Affecting Patient Adherence To Prescribed Aerosol Thmentioning
confidence: 99%